Mechanical Regulation of Epithelial Tissue Homeostasis - Kaliman, Sara; Hubert, Maxime; Wollnik, Carina; Nuic, Lovro; Vurnek, Damir; Gehrer, Simone; Lovrić, Jakov; Dudziak, Diana; Rehfeldt, Florian; Smith, Ana-Suncana (Physical Review X, 2021)
Despite recent efforts to understand homeostasis in epithelial tissues, there are many unknowns surrounding this steady state. It is considered to be regulated by mechanoresponse, but unlike for single cells, this idea remains heavily debated for tissues. Here, we show that changes in matrix stiffness induce a nonequilibrium transition from tubular to squamous Madin-Darby Canine Kidney II tissues. Nonetheless, despite different cell morphologies and densities, all homeostatic tissues display equivalent topologies, which, hence, must be actively targeted and regulated. On the contrary, the mechanoresponse induces dramatic changes in the large-scale organization of the colonies. On stiff gels, this yields an unreported cooperative state of motile cells displaying higher densities than in the arrested homeostatic state, which suggests a more complex relation between cell density and motility than previously anticipated. Our results unequivocally relate the mechanosensitive properties of individual cells to the evolving macroscopic structures, an effect that could be important for understanding the emergent pathologies of living tissues.
CRIS-Team WoS Importer:2021-08-20